1999
DOI: 10.1073/pnas.96.7.3611
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Batis maritima methyl chloride transferase in Escherichia coli

Abstract: Methyl chloride transferase, a novel enzyme found in several fungi, marine algae, and halophytic plants, is a biological catalyst responsible for the production of atmospheric methyl chloride. A previous paper reports the purification of this methylase from Batis maritima and the isolation of a cDNA clone of the gene for this enzyme. In this paper, we describe the isolation of a genomic clone of the methylase gene and the expression of recombinant methyl chloride transferase in Escherichia coli and compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…Plant proteins in which amino acid sequences showed high similarities to Arabidopsis HOL were classi ed as HOL family proteins, including independently characterized methyl chloride transferase (MCT) Hager 1998, 1999), thiol methyltransferase (TMT) (Attieh et al , 2000(Attieh et al , 2002, and halide/thiol methyltransferase (HTMT) (Itoh et al 2009). MCT, TMT, and HTMT proteins are also shown to possess SAM-dependent methyltransferase activity toward not only iodide ions, but also toward ions such as chloride, bromide, thiocyanate, and hydrosul de (Ni and Hager 1999;Attieh et al 1995Attieh et al , 2000Itoh et al 2009). All kinetic analyses of plant HOL family proteins reported to date have been performed using proteins from Brassicales plants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plant proteins in which amino acid sequences showed high similarities to Arabidopsis HOL were classi ed as HOL family proteins, including independently characterized methyl chloride transferase (MCT) Hager 1998, 1999), thiol methyltransferase (TMT) (Attieh et al , 2000(Attieh et al , 2002, and halide/thiol methyltransferase (HTMT) (Itoh et al 2009). MCT, TMT, and HTMT proteins are also shown to possess SAM-dependent methyltransferase activity toward not only iodide ions, but also toward ions such as chloride, bromide, thiocyanate, and hydrosul de (Ni and Hager 1999;Attieh et al 1995Attieh et al , 2000Itoh et al 2009). All kinetic analyses of plant HOL family proteins reported to date have been performed using proteins from Brassicales plants.…”
mentioning
confidence: 99%
“…MCT, TMT, and HTMT proteins are also shown to possess SAM-dependent methyltransferase activity toward not only iodide ions, but also toward ions such as chloride, bromide, thiocyanate, and hydrosul de (Ni and Short Communication DOI: 10.5511/plantbiotechnology.12.0207a Abbreviations: GC-MS, Gas chromatography-mass spectrometry; HPLC, High performance liquid chromatography; MALDI-TOF-MS, Matrixassisted laser desorption/ionization time-of-ight mass spectrometry; SAH, S-Adenosyl-L-homocysteine; SAM, S-Adenosyl-L-methionine; SDS-PAGE, Sodium dodecyl sulfate-polyacrylamide gel electrophoresis. 1999;Attieh et al 1995Attieh et al , 2000Itoh et al 2009). All kinetic analyses of plant HOL family proteins reported to date have been performed using proteins from Brassicales plants.…”
mentioning
confidence: 99%
“…As high concentrations of ions such as Cl Ϫ are often detrimental to plants, halophytic plants are considered to possess various salt tolerance mechanisms. MCT was hypothesized to control and regulate the internal concentration of Cl Ϫ , rich in the habitat in which halophytic plant grows (10,11).…”
mentioning
confidence: 99%
“…The hypotheses concerning the physiological meaning of these enzymes include their involvement in salt tolerance (Ni and Hager 1999) or in metabolizing glucosinolate hydrolysis products such as thiols and thiocyanate (Attieh et al 2000a). The AtHOL1 gene was isolated from Arabidopsis as the MCT homolog, and the T-DNA insertion mutant analyses revealed that AtHOL1 was involved in the synthesis of methyl halides including methyl chloride, methyl bromide, and methyl iodide (Rhew et al 2003).…”
mentioning
confidence: 99%